1975
DOI: 10.1099/00221287-90-2-365
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide as Receptor for Rhizobium Phage 1P

Abstract: INTRODUCTIONThere are only a few papers concerning the sites of phage adsorption in Rhizobium. Barnet & Vincent (1970) suggested that the receptor site for phages 7,7cr, and 8 was associated with the somatic antigen of Rhizobium. Atkins & Hayes (1972) found alterations in lipopolysaccharide (LPS) and lipoprotein (LP) of Rhizobium trifolii mutants that adsorbed phage poorly.To elucidate the attachment site of phage IP to Rhizobium, we studied cell walls and their LPS preparations as phage receptors. METHODSBac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Since many phage receptors of enteric bacteria reside in the LPS (6,18,32,38,39), phage lysis of Rhizobium was studied with the idea that this may be an additional probe for examining the similarity of the LPS of the various Rhizobium strains. However, there is no obvious correlation between phage lysis pattern and LPS composition or immunochemistry (see Tables I and II, and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since many phage receptors of enteric bacteria reside in the LPS (6,18,32,38,39), phage lysis of Rhizobium was studied with the idea that this may be an additional probe for examining the similarity of the LPS of the various Rhizobium strains. However, there is no obvious correlation between phage lysis pattern and LPS composition or immunochemistry (see Tables I and II, and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The partial compositions of the LPS from several strains of R. trifolii and R. leguminosarum have been reported (14,15,21,22,38). Immunochemical studies of the LPS of the two R. trqfolii strains have suggested that these LPS are strain-specific antigenic determinants of these bacteria (14).…”
mentioning
confidence: 99%
“…Rhizobium lipid A appears to be much like that of Escherichia coli and Salmonella species (32, 35,36). As with the enterobacteria, most of the variability of rhizobial LPS resides in the carbohydrate moiety, which may vary as greatly between strains of the same species as between species (4,47). Like LPS of rough mutants of enterobacteria (31) and unlike other rhizobial LPS, R. meliloti LPS contains a high percentage of KDO (47), which, together with other evidence, suggests that it may not have much 0 antigen.…”
mentioning
confidence: 99%
“…Feige and Strim (17) have carried out phage inactivation studies in buffer and broth and have found that neutralization is usually superior in broth. The PhI5o value for 4PLS27 with AK-44 LPS is 0.08 jig/ml, which compares very favorably with the lowest PhI50 values obtained with smoothspecific phages in P. aeruginosa (30,40) and with LPS-specific phages in other genera (23,43,44,52,68).…”
Section: Kropinski Unpublished Data) Phage Opls27mentioning
confidence: 51%